Risk of Social Media for Teens in an Urban Setting - Megan Knowles MD; Sara Hirschfeld Lee MD; MaryAnn O'Riordan PhD; Rina Lazebnik MD (SAGE Publishing, 2014)
Purpose . To describe the self-reported risky behaviors associated with adolescent social media use. Methods . Adolescents ages 13 to 21 years were recruited from a large, urban academic center to complete a written survey regarding social media use. Results are presented as frequencies and percentage; nominal variables were compared using χ 2 analysis. Results . Almost all participants (93%) reported belonging to a social media site. The majority of adolescents (72%) access the Internet with a phone. Nearly half (49%) of participants accept friend requests from strangers, 42% send friend requests to strangers, and 55% of participants report meeting people from social media sites in person. Conclusion . Adolescents self-report engaging in a number of risky behaviors when they use social media. Teenagers' use of social media is an additional behavior that requires attention and monitoring.